PENGGUNAAN METODE LEXICON UNTUK ANALISIS SENTIMEN PADA ULASAN APLIKASI KAI ACCESS DI GOOGLE PLAY STORE - Aryo Nur Utomo; Rahma Dwi Wahyuni (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2022)
Google play store is a digital service platform that functions as an official store that allows users to search and download applications. Google play store also has a feature where users can submit reviews and ratings for apps and digital content. PT. Kereta Api Indonesia abbreviated PT. KAI was launched, namely KAI Access. KAI Access is an application on the Google Play Store that is useful in the process of selling tickets online by utilizing internet technology. However, the review on the KAI Access application is only a sentence without a specific meaning, for that an analysis is needed that can divide classes as user sentiment. This study aims to determine the sentiment analysis of user review data on the KAI Access application on the Google Play Store using the lexicon method. Lexicon is a method used to classify application user opinions into 3 classes, namely, positive, negative, and neutral sentiments. The results showed that the reviews of users of the KAI Access application had negative sentiments, with the highest number and percentage of negative sentiment data, namely 24700 data and a percentage of 60.01%. Keywords: KAI Access, Google Play Store, Sentiment Analysis, Lexicon